2020
DOI: 10.1371/journal.pone.0228224
|View full text |Cite
|
Sign up to set email alerts
|

Early outcome prediction with quantitative pupillary response parameters after out-of-hospital cardiac arrest: A multicenter prospective observational study​

Abstract: We aimed to determine the characteristics of quantitative pupillary response parameters other than amplitude of pupillary light reflex (PLR) early after return of spontaneous circulation (ROSC) and their implications for predicting neurological outcomes early after cardiac arrest (CA). Fifty adults resuscitated after non-traumatic out-of-hospital CA from four emergency hospitals were enrolled. Pupil diameters, PLR, constriction velocity (CV), maximum CV (MCV), dilation velocity (DV), latency of constriction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…The results support the hypothesis that dilation velocity varies with the severity of brain injury. ( 23 - 27 ) These findings extend those of many recent publications that have focused primarily on the NPi, a derived summary score indexed to normal. Lussier et al ( 28 ) recently published that normal DV in critically ill patients ranges significantly (0.3 - 1.1); however, this was a population average and did not utilize machine learning to assess the statistical validity based on groupings.…”
Section: Discussionsupporting
confidence: 81%
“…The results support the hypothesis that dilation velocity varies with the severity of brain injury. ( 23 - 27 ) These findings extend those of many recent publications that have focused primarily on the NPi, a derived summary score indexed to normal. Lussier et al ( 28 ) recently published that normal DV in critically ill patients ranges significantly (0.3 - 1.1); however, this was a population average and did not utilize machine learning to assess the statistical validity based on groupings.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have revealed various factors, such as older age, cardiac arrest occurring at home, initial rhythm other than ventricular tachycardia/ventricular fibrillation, longer duration of no flow, longer duration of low flow, treatment with adrenaline (epinephrine), pupillary response, and a serum lactate level, as prognostic factors for OHCA patients [ 16 20 ]. Despite the prognosis scores proposed using these predictors [ 4 9 ], prognostication of OHCA patients remains challenging, and no single risk-assessment tool has been recommended for the prognostic classification of OHCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed various factors, such as older age, cardiac arrest occurring at home, initial rhythm other than ventricular tachycardia/ventricular brillation, longer duration of no ow, longer duration of low ow, treatment with adrenaline (epinephrine), pupillary response, and a serum lactate level, as prognostic factors for OHCA patients [16][17][18][19][20]. Despite the prognosis scores proposed using these predictors [4][5][6][7][8][9], prognostication of OHCA patients remains challenging, and no single riskassessment tool has been recommended for the prognostic classi cation of OHCA patients.…”
Section: Discussionmentioning
confidence: 99%